The effectiveness of internal audit function and risk management in the Malaysia consumer products industry / Rohaida Ismail ... [et al.] - Ismail, Rohaida; Mohd-Saleh, Norman; Yakob, Rubayah; Hussin, Amariah Hanum (UiTM Cawangan Negeri Sembilan, 2023)
Internal audit function (IAF) plays an increasingly important role in the corporate governance landscape in Malaysia. Besides that, IAF also involved in risk management which providing an assurance on the effectiveness of the risk management process. Bursa Malaysia has mandated that companies have to disclose whether the IAF is performed in-house or outsourced, and the costs incurred in the financial year. Therefore, the purpose of this study is to investigate the association by using these unique data concerning whether IAF have any influence on the enterprise risk management (ERM) effectiveness. The final sample of this study consists of companies from consumer industry which are listed in Bursa Malaysia in the year of 2012 to 2015. Data was further analysed using Ordinary Least Square (OLS) regression analysis to examine the relationship between internal audit function attributes and ERM effectiveness. The findings show that, the amount of investment in internal audit function is significantly related to ERM. However, this study did not find any association between the IAF sourcing arrangement and ERM. The results can only be generalised to the consumer industry companies listed in Bursa Malaysia. This study provides valuable insights into the importance of effectiveness of IAF in monitoring process thus help increase the effectiveness of ERM.